2009
DOI: 10.1021/je900054j
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Stability of Nesquehonite (MgCO3·3H2O) in Mixed NaCl + MgCl2, NH4Cl + MgCl2, LiCl, and LiCl + MgCl2 Solutions

Abstract: The solubility and stability of nesquehonite (MgCO 3 • 3H 2 O) in mixed solutions (NaCl + MgCl 2 , NH 4 Cl + MgCl 2 , LiCl, and LiCl + MgCl 2 ) were measured by using a classic isothermal dissolution method over the temperature range of (298 to 308) K. The concentration investigated for all salts was up to 0.2 mol • dm -3 NaCl, 1.5 mol • dm -3 NH 4 Cl, 0.6 mol • dm -3 MgCl 2 , and 1.5 mol • dm -3 LiCl at ambient temperature. The solubility of MgCO 3 • 3H 2 O phases in all the cases investigated was found to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…9) is ascribed to the antisymmetric stretching of the HCO3 - (Hales et al, 2008;Frost and Palmer, 2011). Nesquehonite has a chemical composition of MgCO3*3H2O (Kloprogge et al, 2003;Dong et al, 2009;Stephan and McGillavry, 1972), but has been described also as Mg(OH)(HCO3)*2H2O (Hales et al, 2008;Hales et al, 2008;Frost and Palmer, 2011). Our IR and Raman results showed the presence of OH -and HCO3 -in the crystal structure of nesquehonite.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…9) is ascribed to the antisymmetric stretching of the HCO3 - (Hales et al, 2008;Frost and Palmer, 2011). Nesquehonite has a chemical composition of MgCO3*3H2O (Kloprogge et al, 2003;Dong et al, 2009;Stephan and McGillavry, 1972), but has been described also as Mg(OH)(HCO3)*2H2O (Hales et al, 2008;Hales et al, 2008;Frost and Palmer, 2011). Our IR and Raman results showed the presence of OH -and HCO3 -in the crystal structure of nesquehonite.…”
Section: Resultsmentioning
confidence: 52%
“…Nesquehonite is a magnesium carbonate mineral with proposed chemical formula either MgCO3*3H2O (Kloprogge et al, 2003;Dong et al, 2009;Stephan and McGillavry, 1972) or Mg(OH)(HCO3)*2H2O (Hales et al, 2008;Hales et al, 2008;Frost and Palmer, 2011), named after a location in Pennsylvania, USA, where found for first time. It is crystallized in the monoclinic crystal structure in space group P21/n, Z = 4 and it has unit cell parameters of a = 7.70Å, b = 5.37Å, c = 12.12 Å and β= 90 o , 45ˊas described by Stephan and MacGillavry (1972) and by Giester et al (2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, analysis by the compiler reveals issues with both studies. Most data of Dong et al 146 refer to systems with two added electrolytes as well, and were not considered. Garrels et al 147 state that, notwithstanding the use of very pure natural magnesite, no conclusive pH at equilibrium of the aqueous magnesium carbonate suspension was recorded, so this reference was neither compiled nor evaluated.…”
Section: -29 Iupac-nist Solubility Data Series 95-1mentioning
confidence: 99%
“…Only two references 145,146 provide data for these systems, both from the same research group. As the MgCO 3 Á3H 2 O þ H 2 O data of this group were accepted, there is reason to believe that the MgCO 3 Á3H 2 O þ H 2 O þ salt data are reliable.…”
Section: Nesquehonitementioning
confidence: 99%
“…Nesquehonite dissociation has been investigated mainly by thermal analysis [25][26][27][28][29][30][31]. Suzuki and Ito [32] monitored decomposition of nesquehonite coupling thermal analysis and X-ray diffraction and suggested that the structure of nesquehonite may be stable at least up to 343-353 K. The results by Ferrini et al [16] extended the thermal stability of this carbonate up to 373 K.…”
Section: Introductionmentioning
confidence: 99%